An investigation of newsroom convergence at the MoAfrika media company in Lesotho and its implications for gatekeeping: a qualitative case study - Senthebane, Teboho (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2009)
This research is based on a case study of MoAfrika, a news organisation that has embraced digitisation to produce and distribute content across three platforms. It draws upon observation and in-depth interviews to show how MoAfrika's embrace of a degree of convergence has led to a fragmentation for journalists whose daily work now include additional responsibilities and pressures of time. While there is an increase in the quantity of news disseminated via radio, newspaper and online, questions arise about the quality of such news produced in a multi-skilled, multiple media news production environment. The result is repurposed stories with little original content and augmented employee workloads without training and compensation. The study examines these issues drawing on theories of gatekeeping and convergence. The decision to include a news story at MoAfrika depends partly on which medium it fits into most easily. News values, deadlines, organisational norms and national trends are some of the considerations which factored into gatekeepers' decisions. Primary decision-making was made within a group which also considered expense and expertise, and where the Managing Editor made the final call and set the frameworks for how content played across the enterprise's three platforms.
Keywords: MoAfrika Convergence (Telecommunication); Mass media -- Management -- Lesotho; Journalism -- Management -- Lesotho; Journalism -- Technological innovations -- Lesotho